Synoptic patterns associated with the highest wind-waves at the mouth of the Río de la Plata estuary - Dragani, Walter Cesar (2013)
In the present paper, the highest wind waves measured at the Río de la Plata mouth were selected to characterize weather patterns associated with the most severe wave conditions in this region. This study was carried out on the basis of wave parameters data series - 14. year long - measured at the Río de la Plata mouth. From the fifteen selected energetic events, twelve were associated with the presence of cyclones located either on the continental shelf (northern 40° S) or on the Uruguayan and southern Brazilian region. On the other hand, three events were linked to the occurrence of post-frontal anticyclones and low pressure systems located in the Southwestern Atlantic Ocean. This last weather pattern is frequently associated with " cold air irruptions" in the Río de la Plata region and, up to the present, it was rarely associated with the presence of the highest waves at the Río de la Plata mouth or adjacent continental shelf. Finally, a common feature observed in almost all the selected cases was the presence of intense wind gusts. This subject is briefly described. © 2013 Published by Elsevier B.V.